An intense 18F-FDG pulmonary microfocus on PET without detectable abnormality on CT: a manifestation of an iatrogenic FDG pulmonary embolus - Ahmad Saad, Fathinul Fikri; Lau, W. F. Eddie (Department of Biomedical Imaging (Radiology), Faculty of Medicine, University of Malaya, 2010)
An incidental finding of an intense focus of 18F-Fluorodeoxyglucose (FDG) pulmonary uptake on positron emission tomography (PET) without detectable lesions on computed tomography (CT) is highly suggestive of FDG microembolus. Its microscopic nature means it is undetectable on CT. It is an artefact attributable to 18F-FDG-tracer contamination at the injection site. This paper reports a case of a 61 year-old lady with a past history of breast carcinoma, in whom follow-up PET/CT images demonstrated an incidental intense FDG pulmonary abnormality. A follow-up PET/CT seven months later demonstrated complete resolution of the abnormality.